USING DISCOVERY LEARNING METHOD TO IMPROVE READING COMPREHENSION OF THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 2 SIGI - Trisnawati Katuwu, Chenia; Darmawan, Darmawan; Anggreni, Afrillia; Marhum, Mochtar (Tadulako University, 2024)
The objective of this research is to prove that using discovery learning methods can improve reading comprehension of the eleventh grade students of SMA NEGERI 2 SIGI. The research applied pre-experimental design. The data were obtained from pre-test and post-test. The population was class XI students at SMA Negeri 2 Sigi. Consisting of 228 students from eight classes. The sample is class IPS 2 as the experimental group. Sample selection was carried out in cluster random sampling. Tests were used to collect data consisting of pre-test and post-test. The test result showed that the average pretest score obtained by the experimental group is 61.55. Then, the average post-test score for the experimental group is 81.45. By applying the 0.05 level significance, the researcher found the sig value obtained (p) was lower than (α) (0,000<0,05) it means that the hypothesis is accepted or using discovery learning method can improve reading comprehension of grade eleventh students of SMA Negeri 2 Sigi. This research implies that the use of discovery learning encourages students to develop research and reflective skills that can be applied across various situations and for teachers to have additional ways of teaching English to their students, especially by using discovery learning methods.